Humanitarian intervention a history - Simms, Brendan; Trim, D. J. B. (David J. B.) (Cambridge University Press, 2011)
"The dilemma of how best to protect human rights is one of the most persistent problems facing the international community today. This unique and wide-ranging history of humanitarian intervention examines responses to oppression, persecution and mass atrocities from the emergence of the international state system and international law in the late sixteenth century, to the end of the twentieth century. Leading scholars show how opposition to tyranny and to religious persecution evolved from notions of the common interests of 'Christendom' to ultimately incorporate all people under the concept of 'human rights'. As well as examining specific episodes of intervention, the authors consider how these have been perceived and justified over time, and offer important new insights into ideas of national sovereignty, international relations and law, as well as political thought and the development of current theories of 'international community'"--